Reinfection rate in a cohort of healthcare workers over 2 years of the COVID-19 pandemic - Guedes, Ana Rubia; Oliveira, Maura S.; Tavares, Bruno M.; Luna-Muschi, Alessandra; Lazari, Carolina dos Santos; Montal, Amanda C.; de Faria, Elizabeth; Maia, Fernando Liebhart; Barboza, Antonio dos Santos; Leme, Mariana Deckers; Tomazini, Francis M.; Costa, Silvia Figueiredo; et al. (Scientific reports, 2023)
In this large cohort of healthcare workers, we aimed to estimate the rate of reinfections by SARS-CoV-2 over 2 years of the COVID-19 pandemic. We investigated the proportion of reinfections among all the cases of SARS-CoV-2 infection from March 10, 2020 until March 10, 2022. Reinfection was defined as the appearance of new symptoms that on medical evaluation were suggestive of COVID-19 and confirmed by a positive RT-PCR. Symptoms had to occur more than 90 days after the previous infection. These 2 years were divided into time periods based on the different variants of concern (VOC) in the city of São Paulo. There were 37,729 medical consultations due to COVID-19 at the hospital’s Health Workers Services; and 25,750 RT-PCR assays were performed, of which 23% (n = 5865) were positive. Reinfection by SARS-CoV-2 was identified in 5% (n = 284) of symptomatic cases. Most cases of reinfection occurred during the Omicron period (n = 251; 88%), representing a significant increase on the SARS-CoV-2 reinfection rate before and during the Omicron variant period (0.8% vs. 4.3%; p < 0.001). The mean interval between SARS-CoV-2 infections was 429 days (ranged from 122 to 674). The Omicron variant spread faster than Gamma and Delta variant. All SARS-CoV-2 reinfections were mild cases.